Incidence and lifetime risk of uterine corpus cancer in Taiwanese women from 1991 to 2010 - Jerry Cheng-Yen Lai; Chia-Sui Weng; Sheng-Miauh Huang; Nicole Huang; Yiing-Jenq Chou; Chien-Chen Wang; Kung-Liahng Wang (Elsevier, 2017)
Objective: Although uterine corpus cancer has been the most common malignancy of the female genital tract in many countries, the lifetime risk of this cancer has not yet been determined among Taiwanese women. The purpose of the study was to describe the change in incidence and the lifetime risk of uterine corpus cancer over a 20-year period from 1991 to 2010 in Taiwan. Materials and methods: We conducted a population-based registry study using the released database (available online) from the Taiwan Cancer Registry. Results: A total of 15,542 women newly diagnosed with uterine corpus cancer were included in this study. The total number of this cancer increased by 5.7-fold from 1991 to 2010. The annual age-specific rate nearly doubled during the past decade (2001-2010) when compared with the previous decade (1991-2000). Incidence rates were highest in women aged 50-59 years, and increasing incidence rates were observed in each age strata starting from 40 years to 85 years and more, after the year 2000. The lifetime risk of being diagnosed with uterine corpus cancer was 0.39% in 1991-1995, 0.54% in 1996-2000, 0.73% in 2001-2005, and 1.12% in 2006-2010 among Taiwanese women. Conclusion: According to the observed changes in incidence rate, the burden of uterine corpus cancer in the general female population is expected to increase in the near future. From a public-health perspective, care providers should develop strategies for the prevention, early detection, and intervention to reduce the rapidly increasing incidence of uterine corpus cancer in Taiwan.